Clinically defining the opioid-exposed birthing person and infant as a dyad to support bedside care, surveillance, and research - Shahla M. Jilani; Jonathan M. Davis; Jonathan M. Davis; David Goldstein; Matthew Grossman; Lauren M. Jansson; Lauren M. Jansson; Mishka Terplan; Hendrée E. Jones; Hendrée E. Jones (Frontiers Media S.A., 2024)
IntroductionAn increased incidence of maternal opioid use disorder (OUD) and neonatal abstinence syndrome (NAS) has prompted recommendations supporting a dyadic approach to care for birthing persons and their infants. However, there are no consensus guidelines outlining how the dyad is clinically defined.MethodsTo examine how the opioid-exposed birthing person-infant dyad has been defined for purposes of data collection and research, a literature review applying the RAND/UCLA Appropriateness Method was conducted.ResultsThe search yielded 320 abstracts, with 110 articles identified as having a dyadic focus. While no articles included a specific definition for the dyad, 33 (30%) contained a descriptive reference to the birthing person-infant dyad. Thematic analysis revealed eight recurring elements characteristic of the dyad: (1) engagement, (2) communication, (3) bonding, (4) attachment, (5) mutual responsiveness, (6) reciprocity, (7) synchrony, and (8) attunement. Integrating these elements revealed the interactional relationship between the opioid-exposed birthing person and infant as the foundational principle that defines the dyad.DiscussionThis definition shifts the focus of the opioid-exposed dyad from two individual patient populations to an interactional relationship that has broad applicability for clinical use, public health data collection, and research considerations.